Subnational State Capacity and the Repression of Protest: Evidence from Mexico. (September 2021) - Sullivan, Heather
While protests occurring in nationally democratic contexts rarely represent fundamental threats to the central state, they still need management when and where they occur. Thus, this paper suggests that, especially in federal countries, to explain the repression of protest, we must examine subnational politics. Subnational political elites, often tasked with protest management, can engage protesters and call for police restraint, but their capacity and authority affect their ability to carry out these tasks. The paper tests the theory using original event-level data on Mexican protests and responses and leverages within-country variations in democracy and state capacity. The paper shows that where subnational governments have bureaucratic capacity and where citizen linkages to the state cause them to see state agents as relevant, problem-solving authorities, protest events are less likely to be managed using a repressive response. In addition, the paper highlights a key difference between explanations of overall human rights violations and repressive responses to protest, namely, that electoral competition is not a significant factor reducing the likelihood of repressive responses to protest.